Social responsibility and good governance - Luna, Alden Reuben B. (Intramuros, Manila, Philippines : Unlimited Books Library Services and Publishing Inc., 2016)
The book deals with the basic conceptual themes and ideas about the interaction of business and society. It will tackle issues such as business and the social, ethical, natural environment; business and stakeholders; and current social issues that somehow affect business operations.
Acknowledgements iii -- The Nature of Morality : Entering the Realm of the Bewildered 1 -- Going Deeper into the Ghetto 53 -- Expanding and Enlightening the Dilemma 93 -- Bringing the Yardstick into the Corporate World 109 -- The Workplace 139 -- The Firm and the Laborers 173 -- The Firm and Consumers 213 -- Ethical Consumerism and Corporate Social Responsibility 247.
Keywords: BUSINESS -- ETHICS